2009
DOI: 10.1080/01612840802557204
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Perceived Burden, Depressive Cognitions, Resourcefulness, and Quality of Life in Female Relatives of Seriously Mentally Ill Adults

Abstract: Providing care and support to a seriously mentally ill (SMI) family member can have deleterious effects on one's health and quality of life. This study explored relationships among perceived burden, depressive cognitions, resourcefulness, and quality of life in 60 African-American and Caucasian women family members of SMI adults. Caucasians reported greater burden than African-Americans; the groups were similar in depressive cognitions, resourcefulness, and quality of life. In Caucasians and African-Americans,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 58 publications
(69 reference statements)
7
50
0
Order By: Relevance
“…The results of that study have been reported elsewhere (Zauszniewski, Suresky, & Bekhet, 2006a, 2006b.…”
Section: Designmentioning
confidence: 59%
“…The results of that study have been reported elsewhere (Zauszniewski, Suresky, & Bekhet, 2006a, 2006b.…”
Section: Designmentioning
confidence: 59%
“…In a follow-up study of the same women, Zauszniewski and colleagues 27 found that African American and white women reported similar resourcefulness skills. However, in African Americans, greater caregiver burden was associated with lower resourcefulness (r = -0.38, p < .0010) and lower resourcefulness correlated with poorer mental health (r = 0.53, p < .001), suggesting that resourcefulness may mediate the adverse effects of caregiver burden on mental health.…”
Section: Resourcefulnessmentioning
confidence: 97%
“…24 They may perceive caregiving as burdensome or stressful, [25][26][27] and they report greater feelings of strain, 27 more stressful life events, 28 and greater disruption in family functioning. 27 Perlick and colleagues 25 found a high use of avoidance coping strategies by family members of persons with mental illness. Although avoidance coping may be a less-than-optimal method for coping, it is possible that this coping method may also be protective; thus, risk factors in one context may be protective in another.…”
Section: Risk/vulnerability Factorsmentioning
confidence: 99%
See 2 more Smart Citations